Peran Dakwah Habib Jafar di Media Sosial dalam Mempengaruhi Sikap dan Perilaku Remaja - Wita, Purnama (Institut Agama Islam Negeri Kerinci, 2024)
Habib Jafar uses the social media platform Instagram to provide lectures, advice and religious teachings to his followers. This research uses a qualitative approach. using the literature review method. This method was chosen because it can provide comprehensive insight into the role of da'wah in fostering youth enthusiasm in the general media regarding Habib Ja''far's teenage behavior and behavior through a review of relevant literature. The term da'wah consists of two syllables, namely term and da'wah. Etymologically, this term means a design, idea or anything that the mind uses to understand something. Da'wah consists of faith or belief that there is only one God and no one is capable of obeying His commands